Flow management strategies for a connected purification process. Issue 9 (13th April 2021) - Goebel, Mathias; Rodrigues, Rui; Pampel, Lars; Rapp, Johanna; Shultz, Joseph; Cui, Huanchun
Abstract: This paper describes different flow management strategies for a connected purification process which includes two polishing steps, virus filtration and tangential flow filtration. Connecting these unit operations avoids introducing large intermediate product pool vessels in small manufacturing facilities. However, a connected‐downstream process requires an elaborate control strategy enabling multiple unit operations to function as a single unit. The key strategy to enable the connected‐downstream process is a robust management of flow disparities among unit operations. During a typical ultrafiltration step, product concentration increases as mass is added to the retentate tank, leading to a permeate flux decline. In a connected‐downstream process, the inlet stream is directly connected to the prior unit operation and any decrease in permeate flow rate could cause a flow disparity. Four different flow management approaches are proposed to manage potential flow disparities and their advantages and challenges are discussed. Bench‐scale results of these strategies are presented and evaluated. Abstract : Moving from discrete to continuous or connected‐downstream processes, flow disparities among unit operations need to be managed in a robust manner. Several flow management approaches are proposed and discussed at example of laboratory data for a connected‐downstream process containing two polishing steps, virus filtration and tangential flow filtration.